Adubação nitrogenada e fosfatada no desenvolvimeno de mudas de uvaia - de Souza, Henrique Antunes [UNESP]; Gurgel, Rafael Lucas da Silva; Teixeira, Glauco Antônio; Cavallari, Ludmilla de Lima [UNESP]; Rodrigues, Helen Cristina de Arruda; Mendonça, Vander (My University, 2009)
Considering the reduced number of works with fertilization of Eugenia uvalha in national literature and being overcome as base the results of the research with fertilization of other fruitful ones, the present work had as objective to study the effect of nitrogen fertilization and phosphorus, in the culture of the Eugenia uvalha. The work was lead in the Department of Agriculture of the Federal University of Lavras, Lavras - MG, in the first semester of 2005. The experiment was adopted the experimental delineation of randomized blocks in factorial project 4 X 4, with four repetitions and 5 plants for parcel, having been 4 doses of phosphorus: 0 kg m-3; 2,5 kg m-3; 5,0 kg m-3; 10,0 kg m-3; using itself as seasoning source the triple superphosphate. Already for nitrogen, the applications proceeded from 10 in 10 days had been used 4 doses in covering being, had been carried through 4 applications. The applications consisted of a solution with urea, in the doses: 0; 0,8; 1,6 e 3,2 Kg m-3, in each application had been added to the polyethylene bags, 20 mL of solution contend the N. had been evaluated the following characteristics: height of the dumb one (cm); root length (cm); leaf number; dry substance of the root and the aerial part (g). For the production of changes of Eugenia uvalha of quality, incorporation to the substratum of up to 1,30 kg m-3 of P2O5 sends regards to it.
Fertilization of nitrogen and phosphorus in production of uvaia seedlings
Keywords: Eugenia uvalha; Fertilizer; Fruit; Nutrition